Phytopharmacology and Clinical Updates of Berberis Species Against Diabetes and Other Metabolic Diseases - Belwal, Tarun; Bisht, Aarti; Devkota, Hari Prasad; Ullah, Hammad; Khan, Haroon; Pandey, Aseesh; Bhatt, Indra Dutt; Echeverría, Javier (Frontiers in Pharmacology, 2020)
The incidences of diabetic mellitus and other metabolic diseases such as hypertension and hyperlipidemia are increasing worldwide; however, the current treatment is not able to control the rapidly increasing trend in diabetes mortality and morbidity. Studies related to the effectiveness of extracts and pure compounds obtained from plants have shown promising responses in preclinical and clinical studies related to these metabolic diseases. Plants belonging to the genus Berberis (Family: Berberidaceae) are widely distributed with nearly 550 species worldwide. Extracts and compounds obtained from Berberis species, especially Berberine alkaloid, showed effectiveness in the management of diabetes and other metabolic diseases. Various pharmacological experiments have been performed to evaluate the effects of Berberis extracts, berberine, and its natural and chemically synthesized derivatives against various cell and animal disease models with promising results. Various clinical trials conducted so far also showed preventive effects of Berberis extracts and berberine against metabolic diseases. The present review focuses on i) research updates on traditional uses, ii) phytopharmacology and clinical studies on Berberis species, and iii) active metabolites in the prevention and treatment of diabetes and other metabolic diseases with a detailed mechanism of action. Furthermore, the review critically analyzes current research gaps in the therapeutic use of Berberis species and berberine and provides future recommendations.